Indigenous peoples rights and conflict-situation in the oil-producing states of Nigeria : the globalization connection and activities of the multinationals - Lasbrey, Ononiwu Chukwuka (2009)
This paper analyses some salient or key issues surrounding the features of youth restiveness and state of instability around the Niger Delta region in Nigeria. The research is undertaken against the background that the region generates a good measure of income to both the federal government and other local and international oil prospecting companies estimated at several billions of dollars annually and yet the inhabitants of the area complain bitterly of neglect and harms to their environments, social, cultural, economic and political rights. Many studies have been done in the past on the lingering crisis, with very good results showing some factors that underline the conflict. (Ukeje,2001;Obi,1997,2006;Odum, 1996;Aneej, 2004;Ohia, 2006;Owolabi and Okwechime:2007..) However, this paper attempts to deep more into the core value-error underpinnings and clash of interests between moral economics and exploitative capitalism that conditions the state of hostility in the region of late. The paper without any pretensions explores the networks of alliance that collude to deny the locals their fair shares of good-life and wellness. The research pursues this within the theoretical context of psychosocial feelings of neglect and human rights deprivations that in-turn triggers a revolutionary approach to justice seeking after the failures of non-violence methods of the past. To carry out the research, the paper adopts a use of mixed-method research where both qualitative and quantitative data are synthesized into single frame of analysis and findings that show a clear statement of underdevelopment crisis in the region and the paradox of poverty in midst of plenty and the tensions it is generating at the moment in the region. The situation is strongly attributed to the vortex of clash of values between moral economics and brute-capitalism and the local youths revolutionary ideologies channeled towards upturning the historical networks and alliances that collude to deny them their fair share of basic human and environmental rights. The paper does not simple lay developmental crisis on the agents of investment-capital abroad nor does it “close-eye” to the internal questions as corruption, good governance and accountability issues, but it strongly posits that the alliance of both domestic and external combines permeate this feelings of social injustices in the region and the present resort to militant overthrow of sources considered enemies to the people and their environments. The result of the research cuts across different crosscutting themes within the comprehensive and broad developmental frameworks, from a human rights based approach to climatic sustainability issues as well as other tenets of the holistic-developmental ideas.